The plots against the president : FDR, a nation in crisis, and the rise of the American right - Denton, Sally (Bloomsbury Press, 2012)
An assessment of the political and physical dangers faced by the newly elected President Roosevelt in 1933 profiles such adversaries as would-be assassin Giuseppe Zangara and populist demagogues Huey Long and Charles Coughlin.